Benthic dinoflagellates assemblages Associated with Ciguatera Fish Poisoning (CFP) at Fringing Coral Reff Ecosystem of Perhentian Islands, Malaysia / Lee Li Keat - Lee , Li Keat (2019)
Ciguatera fish poisoning (CFP) is a foodborne disease associated with seafood contamination by ciguatoxins (CTXs) produced by Gambierdiscus species, which known to assimilate and metabolize through multiple trophic levels from herbivorous fish to larger finfish predators. However, the source and fate of CTXs into the marine food web remained ambiguous. Benthic dinoflagellates are known to be closely associated with the benthic biotic substratum such as seaweed, seagrass, turf algae and corals where these substrata are served as a feeding ground for reef inhabitants (reef fishes, invertebrates). Thus, the distribution and natural assemblages of benthic dinoflagellates on the bottom substratum of coral reef ecosystem becomes one of the key elements to trace the origin of ciguatoxin transfer. This study aims to understand the CTX transfer into the marine food web by investigating the distribution and natural assemblages of benthic harmful dinoflagellates in the different substratum. The diversity of benthic dinoflagellate was investigated. The study was conducted in Perhentian Islands (5°54'13.44"N, 102°44'49.27"E), located off the coast of Terengganu, Malaysia. A total of 243 samples were collected from five sampling sites over the period of April 2016 to May 2017 using an artificial substrate sampling method (fibreglass screens with a dimension of 10.2 × 15.2 cm). The benthic habitats were characterized by using CoralNet. Cells of benthic dinoflagellates, Gambierdiscus, Ostreopsis, Coolia, Amphidinium and Prorocentrum were enumerated microscopically. The species were further identified by advanced morphological and molecular characterizations. The results revealed the presence of three species of Gambierdiscus, four species of Coolia, two species of Amphidinium, five species of Prorocentrum, a species of Ostreopsis, and a species of Gymnodinium; this included the first record of C. palmyrensis, C. cf. canariensis, Gymnodinium dorsalisculcum, and A. cf. massartii in our waters. The results showed a depth gradient of benthic dinoflagellate distribution and abundance, where Gambierdiscus, Ostreopsis and Amphidinium abundances decreased with depth (>10 m). Coolia and Prorocentrum were commonly found distributed throughout the depths investigated. Results of the Kruskal-Wallis test revealed that benthic dinoflagellates demonstrated different habitat preferences spanning from areas with sandy patches and corals to macrophyte coverages. Prorocentrum was the dominant group; it was found across various types of the substratum but particularly preferred the substratum with high sand covers. In contrast, Ostreopsis was abundant in shallower water which showed preference towards macrophyte-covered substratum and turf algae assemblage. Gambierdiscus demonstrated a preference towards macroalgae such as Jania spp. and turf algae assemblages. Ciguatoxicity of two species of Gambierdiscus, G. caribaeus and G. balechii, were confirmed through a cytotoxicity assay, neuroblastoma-2a assay. In conclusion, benthic dinoflagellates assemblages displayed distinct community structure and compositions across different bottom substrates. Habitat preferences of Gambierdiscus on substratum with high turf algal covers may promote ciguatoxin flux from the bottom substrates into the marine food web as turf algae have high colonization rate and high palatability.